Coactivator-associated arginine methyltransferase 1 promotes cell growth and is targeted by microRNA-195-5p in human colorectal cancer - Meifeng Zhang; Wei Wu; Ming Gao; Jie Zhang; Xinde Ding; Ronghua Zhu; Haiqun Chen; Zhewei Fei (Tumor Biology)
The pathogenesis of colorectal cancer remains poorly understood. Here, we show that coactivator-associated arginine methyltransferase 1 is frequently upregulated in colorectal cancer tissues and promotes cell growth in vitro and in vivo. Using bioinformatics-based prediction and luciferase reporter system, we found that coactivator-associated arginine methyltransferase 1 is post-transcriptionally targeted by microRNA-195-5p in colorectal cancer. Ectopic expression of microRNA-195-5p led to the suppression of the coactivator-associated arginine methyltransferase 1 3′-untranslated regions activity and downregulation of the endogenous coactivator-associated arginine methyltransferase 1 protein in colorectal cancer cells. Expression analysis verified that microRNA-195-5p was markedly downregulated in human colorectal cancer tissues, which was negatively correlated with the elevated levels of coactivator-associated arginine methyltransferase 1 protein. Enhanced levels of microRNA-195-5p in colorectal cancer cells resulted in a sharp reduction of cell proliferative and colony-formative capacities in vitro. Remarkably, restoration of coactivator-associated arginine methyltransferase 1 in microRNA-195-5p-transfected colorectal cancer cells partially abrogated the inhibition of cell proliferation and colony formation mediated through microRNA-195-5p. These data confirm that microRNA-195-5p might function as an anti-tumor microRNA in colorectal cancer exerting critical control over coactivator-associated arginine methyltransferase 1 expression. The newly identified microRNA-195-5p/coactivator-associated arginine methyltransferase 1 axis may act as a novel promising therapeutic target for colorectal cancer treatment.